Differential Pulse Voltammetric Determination of Folic Acid Using a Poly(Cystine) Modified Pencil Graphite Electrode - Dokur, Ebrar; Gorduk, Ozge; Sahin, Yucel (TAYLOR & FRANCIS INC, 2020)
The electropolymerization of L-cystine was performed on a pencil graphite electrode (PGE) in order to improve the redox properties for the determination of folic acid (FA). The characterization studies of the poly(cystine)/PGE were performed by cyclic voltammetry and electrochemical impedance spectroscopy (EIS). The surface morphology of the poly(cystine)/PGE was examined by scanning electron microscopy (SEM). The performance of poly(cystine)/PGE for the determination of folic acid was investigated using differential pulse voltammetry (DPV) and cyclic voltammetry (CV). According to the results, the electrochemical response of folic acid increased significantly on the poly(cystine)/PGE. The poly(cystine)/PGE showed a linear response for the concentrations range from 1.0 mu M to 100 mu M for the oxidation of folic acid. The (poly(cystine)/PGE) demonstrated a favorable sensitivity for the electrochemical determination of folic acid. The limits of detection (LOD) and quantitation (LOQ) were determined to be 0.43 mu M and 1.45 mu M at signal-to-noise ratios of 3 and 10, respectively. The determination of folic acid was successfully performed on the poly(cystine)/PGE in orange juice.
Keywords: Folic acid (FA); poly(cystine); pencil graphite electrode (PGE); cyclic voltammetry (CV); differential pulse voltammetry (DPV); GLASSY-CARBON ELECTRODE; ASCORBIC-ACID; URIC-ACID; ELECTROCHEMICAL DETERMINATION; LEVEL DETERMINATION; GOLD NANOPARTICLES; PASTE ELECTRODE; ONE-STEP; NANOTUBES; DOPAMINE; Chemistry